Implementation of Plant Disease Recognition Using Deep Learning in Telegram Messenger - Yuliansyah, Harry; Hartanto, Rudy; Soesanti, Indah (2023 1st International Conference on Advanced Engineering and Technologies (ICONNIC), 2023)
Agriculture has an essential role in the national economic development structure. It is necessary to detect plant diseases as early as possible to prevent losses to increase production yields. Recent advances in image processing and artificial intelligence propose a novel method of plant disease recognition. The primary challenge in integrating the CNN model into the Telegram messenger bot lies in synchronizing the CNN services to efficiently receive inputs sent via the Telegram API. Resolving this challenge is the focal point of this research. This study has developed a new plant diseases method using telegram messenger based on deep learning and a convolutional neural network. The user can easily upload their plant image through telegram messenger. The response was immediately sent back after the server processed the input image. Experimental results show the performance system is fast response and highly accurate.